Apologies by the second language speakers in an educational setting / Noorzan Hj Mohd Noor (Universiti Teknologi MARA, Terengganu, 1991)
Previous studies have provided evidence which suggests that second language (L2) learners are faced with the great risk of offending their interlocutors or of miscommunication when performing face-threatening acts for example as in apologies. In this paper, [an assignment which was done for the graduate studies at an American University], the act of apologizing as realized in the speech of Malay and Chinese university students who are learners of English as a second language is compared to native speaker performance (Americans)